The Problematics of Qur'an Teaching in Singapore's Half-Time Madrasah - Tokyan, Muhaimin Bin; Zamsiswaya (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The half-time madrasah is an outgrowth of the earliest institutions of Islamic learning in Singapore. Half-term madrasah offers religious education for students attending mainstream schools. The half-term madrasa curriculum uses an Islamic religious education model called "Program aLIVE," or Learning Islamic Values Every Day. However, it is observed that students who have the potential to read the Qur'an well and correctly are low. This article tries to explain some of the problems that become obstacles to learning the Qur'an in Madrasah Separuh Masa. The research method used is a type of qualitative research with a literature study approach. The data used is sourced from observation, interviews, and documentation. The results show that there are several challenges that become problematic in the process of teaching the Qur'an at Madrasah Separuh Masa Singapore. First, the lack of learning time, limited human resources, the difficulty of building student motivation, and Qur'an teaching methods. Abstrak Madrasah separuh masa merupakan hasil perkembangan dari institusi pembelajaran agama Islam paling awal di Singapura. Madrasah separuh masa menawarkan pendidikan agama bagi siswa yang mengikuti sekolah umum. Kurikulum madrasah separuh masa menggunakan model Pendidikan Agama Islam yang disebut dengan “Programme aLIVE” atau Learning Islamic Values Every Day. Namun demikian, dari hasil pengamatan didapat hasil bahwa siswa yang berpotensi bisa membaca Al-Qur’an dengan baik dan benar rendah. Artikel ini mencoba memaparkan beberapa problem yang menjadi kendala dalam pembelajaran Al-Qur’an di Madrasah Separuh Masa. Metode penelitian yang digunakan adalah jenis penelitian kualitatifdengan pendekatan studi pustaka. Data yang digunakan bersumber dari observasi, wawancara, dan dokumentasi. Hasil penelitian memperlihatkan bahwa ada beberapa tantangan yang menjadi problematika dalam proses pengajaran al-Qur’an di Madrasah Separuh Masa Singapura. Pertama, kurangnya waktu pembelajaran, keterbatasan sumber daya manusia, sulitnya membangun motivasi siswa, dan metode pengajaran Al-Qur’an.